The Arabidopsis Lectin Receptor Kinase LecRK-V.5 Represses Stomatal Immunity Induced by Pseudomonas syringae pv. tomato DC3000 - Desclos-Theveniau, Marie (Public Library of Science, 2012)
Stomata play an important role in plant innate immunity by limiting pathogen entry into leaves but molecular mechanisms regulating stomatal closure upon pathogen perception are not well understood. Here we show that the Arabidopsis thaliana L-type lectin receptor kinase-V.5 (LecRK-V.5) negatively regulates stomatal immunity. Loss of LecRK-V.5 function increased resistance to surface inoculation with virulent bacteria Pseudomonas syringae pv tomato DC3000. Levels of resistance were not affected after infiltration-inoculation, suggesting that LecRK-V.5 functions at an early defense stage. By contrast, lines overexpressing LecRK-V.5 were more susceptible to Pst DC3000. Enhanced resistance in lecrk-V.5 mutants was correlated with constitutive stomatal closure, while increased susceptibility phenotypes in overexpression lines were associated with early stomatal reopening. Lines overexpressing LecRK-V.5 also demonstrated a defective stomatal closure after pathogen-associated molecular pattern (PAMP) treatments. LecRK-V.5 is rapidly expressed in stomatal guard cells after bacterial inoculation or treatment with the bacterial PAMP flagellin. In addition, lecrk-V.5 mutants guard cells exhibited constitutive accumulation of reactive oxygen species (ROS) and inhibition of ROS production opened stomata of lecrk-V.5. LecRK-V.5 is also shown to interfere with abscisic acid-mediated stomatal closure signaling upstream of ROS production. These results provide genetic evidences that LecRK-V.5 negatively regulates stomatal immunity upstream of ROS biosynthesis. Our data reveal that plants have evolved mechanisms to reverse bacteria-mediated stomatal closure to prevent long-term effect on CO(2) uptake and photosynthesis.